Usefulness of Capillary Gel Electrophoresis-Based PCR for Detection of Clostridioides difficile Strains with Hypervirulent Ribotypes - Tomasz Bogiel; Alicja Dura; Marcin Woźniak; Agnieszka Mikucka; Piotr Kanarek (Gels, 2024)
Clostridioides difficile is a complex of anaerobic bacteria responsible for the epidemics of post-antibiotic diarrhea as one of the examples of CDI (Clostridioides difficile infection). As many as 70% of cases concern hospitalized patients, particularly those in intensive care units. Ribotyping is one of the most common methods for differentiating bacterial strains. The purpose of this work was to show the effectiveness of the gel electrophoresis-based PCR ribotyping method and the Webribo database for typing C. difficile isolates, including the hypervirulent 027 ribotype. DNA samples extracted from 69 C. difficile strains with previously marked genotypes were included in this study. PCR was performed using 16S–23S primers, and capillary gel electrophoresis was performed on the Applied Biosystem 3130xl Genetic Analyzer. The Webribo database was applied for ribotype assignment. Out of 69 samples, 48 belonged to already known ribotypes, 13 represented new ribotypes and 8 was indicated as similar to the existing ones, having some differences. Capillary gel electrophoresis-based PCR is an effective method for the differentiation of C. difficile ribotypes and can be recognized as a very useful tool in epidemiological studies, while the Webribo database is a useful and an accessible database for a quick analysis of C. difficile ribotypes.